Strategic Partnership between Russia and India from the Perspective of National Elites - Alexey Kupriyanov (Vestnik MGIMO-Universiteta)
The focus of the article is the analysis of the prospects of the relationship between Russia and India. The author examines the attitudes of the elites in both countries towards each other, using historical sociology, the theory of cultural hegemony, and post-colonialism to explain the formation and perspectives of these elites. The objective and subjective economic and political conditions have, until recently, hindered any genuine efforts towards bringing the two countries closer, as both sides perceived the West as a more promising partner. This attitude has been shaped by historical factors, such as the formation of the Indian elites under the influence of British political, economic, and military culture, and the reckless admiration of the victors of the Cold War by the Russian elites, which attempted to abandon the Soviet legacy after the collapse of the USSR. Despite declarations of strategic interest in forming a polycentric world and developing bilateral Russian-Indian relations, economic ties have not supported these intentions. However, the conflict in Ukraine and the imposition of Western sanctions have compelled the Russian elites to re-evaluate their priorities. They have been faced with a choice: either to return to a Western orientation, which could lead to internal discontent, or to build stronger ties with China or India. The path chosen will depend on the position of the Indian elites, who have the freedom to take a neutral stance in a conflict far from their borders, and on the outcomes of the Ukrainian crisis.